Quality of life in ethnically diverse neighbourhoods - Davies, Rhys.; Wilkins, Clair; Harrison, Eric.; European Foundation for the improvement of living and working conditions (Λουξεμβούργο : Υπηρεσία Επισήμων Εκδόσεων των Ευρωπαϊκών Κοινοτήτων, 2011)
Many European countries have experienced a high level of immigration from all parts of the world in the past two decades. The driving forces behind this have included rapid population growth and high rates of poverty in developing countries and strong demand for unskilled labour in Europe's agricultural and construction industries. This report presents the results of a programme of research that analyses the quality of life in ethnically diverse neighbourhoods in EU15 countries (Member States before the 2004/7 accession) based on the 2007 European Quality of Life Survey (EQLS). A description of the 2007 EQLS, including its approach to measuring and monitoring quality of life, is provided in Eurofound (2009). The focus of the analysis is on the comparative situation of neighbourhoods in which respondents to the EQLS state that the share of the population from racial or ethnic groups different from the majority is relatively high ('high-diversity neighbourhoods'). The analysis focuses on the EU15 and 10 selected countries within it. The selection of these countries (discussed below) was pragmatic and reflects the available sample size within the EQLS of respondents who report that they live in these areas.
Περιέχει βιβλιογραφία και ευρετήριο.
Ηλεκτρονικό βιβλίο
Keywords: Quality of life -- European Union countries; Electronic books